Glucose microfluidic fuel cell using air as oxidant. (28th December 2016) - Escalona-Villalpando, R.A.; Dector, A.; Dector, D.; Moreno-Zuria, A.; Durón-Torres, S.M.; Galván-Valencia, M.; Arriaga, L.G.; Ledesma-García, J.
Abstract: A bioanode was constructed using glucose oxidase enzyme (GOx) supported on multiwalled- carbon nanotubes (MWCNTs) in the presence of glutaraldehyde (GA) (GOx/MWCNTs-GA) and evaluated in an air-breathing hybrid glucose microfluidic fuel cell (HG-μFC). The air-breathing HG-μFC operated under physiological conditions (5 mM glucose at pH 7 with an air-exposed cathode) delivers an open circuit value of 0.72 V with 610 μW cm −2 of maximum power density, and shows potential possibilities to develop future implantable applications. Highlights: A hybrid glucose microfluidic fuel cell with an air-exposed cathode is tested. Glucose oxidase enzyme is used as anodic biocatalyst and Pt/C as cathodic electrode. Carbon nanotubes favour the direct electron transfer in the bioanode. The micro-device delivers the highest power density to date reported.